Efektivitas Konseling Realita untuk Mengembangkan Kompetensi Intrapersonal Remaja - Herny Novianti (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2019)
This research aimed to produce effectiveness of reality counseling for developing adolescence intrapersonal competence. The method of research used quasi-experimental research design with one group pretest-posttest. The sample in this study were adolescence of LKSA Melati., aged 15-17 years, totaling 28 adolescents. Data was collected by intrapersonal competence instrument, arranged on the aspects of Self Knowledge, Self Direction, and Self Esteem. The results showed Reallity counseling effective to develop adolescence intrapersonal competence, increased of five indicators of Self-understanding, Self-acceptance, Self-regulation, Self-control, Self Confidence. Indicators were not significant for Self Image, and Self-utilization Recommendations showed for guidance and counseling study program, child social welfare institution (LKSA) and further research.